Learning Area Management (A Site Study At Tk Pembina Magelang) - Darmiatun, Darmiatun (2012)
The objectives of the research are to describe (1) the characteristics of teacher activities in learning Area at TK Pembina Magelang. (2) the characteristics of students activities in Learning Area at TK Pembina Magelang It is descriptive qualitative research and ethnography design was conducted in TK Pembina Magelang. The data are in the forms of information consisting of systematic thought, sentences, and experience based on specific context. The data sources are event, document, and informant. Techniques used in data collection are in-depth interview, documentation and observation. Data analysis of this research is (1) data collection, (2) data reduction, (3) data display, and (4) conclusion. The validity test of the data uses the credibility, transferability, conformability and dependability. The research results show (1) Activities of teacher in the learning area at TK Pembina Magelang conducted in accordance with the procedure. Teachers carry out the activity that starts from the preparation of lesson plans, learning management which includes managing / structuring classes and organizing student / child, and conducting assessments in accordance with the characteristics of children, child development stage, environmental conditions and facilities existing in kindergarten. (2) Activities of students / children in the learning area at TK Pembina Magelang conducted in accordance with the level of development, needs and interests. Students / children carry out activities in the learning area with an allocation of 2.5 hours or 150 minutes. Students carry out core activities in the areas provided by the teacher in a day at least 4 areas.